Effects of immunocastration on the nutrient responses, carcass traits and meat quality of growing pigs (Sus crofa domesticus) - Needham, Tersia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2014.